The effects of aging on biceps brachii muscle fibers: a morphometrical study from biopsies and autopsies - Ana Cláudia Mattiello-Sverzut; Leila Chimelli; Maria Silvia de Assis Moura; Silvia Teixeira; José Alberto Mello de Oliveira (Arquivos de Neuro-Psiquiatria, 2003)
OBJECTIVES: In order to study the morphology and size of muscle fibers, cross sections of biceps brachii samples from autopsies, up to 9 hours after death, and biopsies of 72 subjects were compared. The subjects aged 13 to 84 years in both sexes. METHODS: The samples obtained from autopsies (n=47) were from subjects with sudden death, or who died after acute disease without evidence of neuromuscular involvement. The biopsies (n=25) were from patients with symptoms suggestive of inflammatory or metabolic myopathy, not confirmed morphologically. The lesser diameter of muscle fibers was measured using the ATPase reaction. RESULTS: Morphological analysis showed that aging changes were present from the sixth decade in autopsies, and consisted of atrophy and/or type-grouping. The statistical models adjusted for females in both autopsies and biopsies were linear straight with no variation in fiber size with increasing age. The models adjusted for males in both groups were quadratic, indicating that age influenced the size of different type fibers. In males type 2 were larger than type 1 fibers, and than fibers in females. CONCLUSIONS: These values might be useful as controls, helping interpretation of changes in fiber size in samples obtained from biopsies and autopsies.